Pengaruh Fasilitas dan Pengalaman Pelanggan terhadap Minat Membeli Ulang Jasa Transportasi PT Chandra Adi Dharma Raya - Lanna Sari Juliana Pasaribu; Syafrida Hafni Sahir; Ihsan Effendi (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
Abstract: This study intends to ascertain how PT Chandra Adi Dharma Raya's amenities and customer experience affect the intention to repurchase its transportation services. Information was gathered via a poll from 95 respondents who had previously taken the bus service to Simangambat District, North Padang Lawas, using a quantitative associative technique. The sample was chosen by the use of purposeful sampling. Multiple linear regression, conventional hypothesis testing, and validity and reliability testing were all employed in the data analysis process. The findings demonstrated that repurchase intention was significantly and favorably impacted, partially and concurrently, by facility quality and customer experience. The regression model obtained was Y = 3.123 + 0.304X₁ + 0.401X₂. The t-test results showed that facilities (t = 3.067, p = 0.003) and customer experience (t = 3.987, p = 0.000) each had a significant influence. The F-test results confirmed a simultaneous effect (F = 74.875, p < 0.05). 61.7% of the variance in repurchase intention was explained by the two independent variables, as indicated by the coefficient of determination (R2), which is 0.617. According to the survey, in the transportation services sector, improved services and greater customer satisfaction can boost client loyalty.